Implikasi Akta Nominee Sebagai Dasar Permohonan Pengampunan Pajak - Agung, Imelda; Kawuryan, Endang Sri (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2017)
Abstract: Tax forgiveness aims to attract repatriation funds belonging to Indonesian citizens who are abroad to be withdrawn to Indonesia. This tax forgiveness is also intended for th e taxpayers in Indonesia to acknowledge the truth of the real property owned. For the taxpayers who buy land or buildings who still use the nominee’s name can recognize the property again and reported as legitimate property, so that the taxpayer can report and pay the tax in accordance with the real circumstances. The tax forgiveness program is an opportunity for the abolition of tax payable, not subject to tax administration sanctions and criminal sanctions in taxation, by disclosing property by paying ransom as regulated in Law Number 11 on Tax Amnesty. The principle of composing the Tax Forgiveness Law is the principle of legal certainty, the principle of justice, the principle of expediency, and the principle of national interest. Taxpayers who already have assets or assets not yet certified must report it and pay the ransom. Abstrak: Pengampunan pajak bertujuan menarik dana repatriasi milik WNI yang berada di luar negeri agar dapat ditarik kembali ke Indonesia. Pengampunan pajak ini diperuntukkan juga bagi Wajib Pajak di Indonesia agar mau mengakui kebenaran harta yang dimiliki sesungguhnya. Bagi para Wajib Pajak yang membeli tanah atau dan bangunan masih memakai nama orang lain (nominee) dapat mengakui kembali harta tersebut dan dilaporkan sebagai harta sahnya, sehingga Wajib Pajak dapat melaporkan dan membayar pajaknya sesuai dengan keadaan yang sesungguhnya. Program pengampunan pajak merupakan kesempatan untuk penghapusan pajak yang terutang, tidak dikenai sanksi administrasi perpajakan dan sanksi pidana di bidang perpajakan, dengan cara mengungkap harta dan membayar uang tebusan sebagaimana diatur dalam Undang-Undang Nomor 11 Tentang Pengampunan Pajak (Tax Amnesty). Adapun asas penyusunan Undang-Undang Pengampunan Pajak adalah asas kepastian hukum, asas keadilan, asas kemanfaatan, dan asas kepentingan nasional. Para Wajib Pajak yang telah mempunyai harta atau aset belum bersertifikat tetap harus melaporkannya dan membayar uang tebusan.